Hubungan Tingkat Pengetahuan dengan Kepatuhan Konsumsi Tablet Tambah Darah (TTD ) pada Remaja Putri di SMP Negeri 6 Kota Kupang - Alifah Fatira Islamiyah; Kartini Lidia; Anita Lidesna Shinta Amat; Gotfrieda Patiencia Taeng-Ob Adang (Jurnal Ilmiah Kedokteran dan Kesehatan, 2026)
Anemia is a condition when the hemoglobin (Hb) level in the blood is less than normal. The most common cause of anemia is iron deficiency. Adolescent girls are at risk of anemia due to their rapid growth and lack of iron intake. Anemia in adolescent girls has various adverse effects both in the short and long term. The Indonesian government prevents anemia in adolescent girls with a program to provide blood supplement tablets to fulfill iron intake. This program is implemented through schools by providing free blood supplement tablets, one tablet per week. Of 80.9% of adolescent girls who received blood supplement tablets at school, only 1.4% consumed ≥ 52 tablets per year. One of the factors that influence adherence behavior is knowledge. Objective: This study aims to determine the relationship between the level of knowledge and compliance with the consumption of blood supplement tablets in adolescent girls at SMPN 6 Kupang. Method:  This research was an analytical observational research with a cross-sectional approach. This study was conducted on adolescent girls from SMPN 6 Kupang using a knowledge questionnaire and the Morisky Medication Adherence Scale-8 (MMAS-8) questionnaire. The sampling technique used stratified random sampling with 106 respondents who fulfilled the criteria of inclusion and exclusion. This study was analyzed by univariate and bivariate using chi-square test. Result: The results of the study were on 106 respondents, 64 respondents (60.4%) had poor knowledge and 42 respondents (39.6%) had good knowledge. Based on adherence to taking blood supplement tablets, 66 respondents (62.3%) had low adherence, 24 respondents (22.6%) had moderate adherence and 16 respondents (15.1%) had high adherence. The results of the chi-square test obtained p = 0.000 (p < 0.05). Conclusion: There is a significant correlation between the level of knowledge and adherence to the consumption of blood supplement tablets among adolescent girls at SMPN 6 Kupang.